The Interface Between Indigenous and Non-Indigenous Systems of Knowing and Learning: a Report on a Dharug Language Programme - Green, Richard (Ricky); Oppliger, Amanda (The Australian Journal of Indigenous Education, 2007)
Abstract This paper reports on the processes experienced in the development of a language programme in a high school in the western suburbs of Sydney in 2006 and represents the ideas and views of the two key participants. We consider the different perspectives held by the key participants on the project and how these need to be worked through in order to come to a place where the two (or more) systems of knowing and learning can be symbiotic rather than pushing against one another. The two systems being referred to are, in brief, a Western academic position, held by the linguist on the project, and an Indigenous intuitive position, held by the language tutor on the project. We report on the steps forward and backward in this process and how the participants felt and dealt with the emotional and intellectual demands incurred throughout the process. Much of this “two steps forward, one step back” process has resulted from the struggle for the non-Indigenous linguist to understand the Indigenous tutor’s knowledge, input and feelings. Likewise the tutor had to come to understand the linguist’s knowledge base and what she was trying to do. We hope that this paper will open up many issues for consideration and discussion such as collaborative research, teaching and learning and working as a partnership.